2019
DOI: 10.1371/journal.pgen.1008532
|View full text |Cite
|
Sign up to set email alerts
|

Genetic determinants of genus-level glycan diversity in a bacterial protein glycosylation system

Abstract: The human pathogens N. gonorrhoeae and N. meningitidis display robust intra-and interstrain glycan diversity associated with their O-linked protein glycosylation (pgl) systems. In an effort to better understand the evolution and function of protein glycosylation operating there, we aimed to determine if other human-restricted, Neisseria species similarly glycosylate proteins and if so, to assess the levels of glycoform diversity. Comparative genomics revealed the conservation of a subset of genes minimally req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(43 citation statements)
references
References 63 publications
0
32
0
Order By: Relevance
“…Recently, we reported that a single-loci was responsible for the generation of the O-linked glycans in B. Cenocepacia and that this loci is conserved across the Burkholderia (23). Although these results support that Burkholderia species use similar glycans, it has been noted that within other bacterial genera extensive glycan heterogeneity exists (25,26,29,32). As glycan heterogeneity can be challenging to predict, we reasoned that open searching would provide a means to assess the similarities in glycans used across Burkholderia species.…”
Section: Resultsmentioning
confidence: 74%
“…Recently, we reported that a single-loci was responsible for the generation of the O-linked glycans in B. Cenocepacia and that this loci is conserved across the Burkholderia (23). Although these results support that Burkholderia species use similar glycans, it has been noted that within other bacterial genera extensive glycan heterogeneity exists (25,26,29,32). As glycan heterogeneity can be challenging to predict, we reasoned that open searching would provide a means to assess the similarities in glycans used across Burkholderia species.…”
Section: Resultsmentioning
confidence: 74%
“…Over the last decade, glycopeptide-based enrichment approaches have increasingly been used to track and characterise microbial glycosylation events [42,44,64,76]. Although enrichment strategies enable high-throughput analysis of glycosylation, we demonstrate here that hydrophilic enrichment provides only partial access to some microbial glycoproteomes.…”
Section: Discussionmentioning
confidence: 80%
“…Recently, we reported that a single-loci was responsible for the generation of the O -linked glycans in B. Cenocepacia and that this loci is conserved across the Burkholderia [23]. Although these results support that Burkholderia species utilise similar glycans, it has been noted that within other bacterial genera extensive glycan heterogeneity exists [25, 26, 29, 32]. As glycan heterogeneity can be challenging to predict, we reasoned that open searching would provide a means to assess the similarities in glycans used across Burkholderia species.…”
Section: Resultsmentioning
confidence: 99%